2016
DOI: 10.1038/mp.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Transiently increased glutamate cycling in rat PFC is associated with rapid onset of antidepressant-like effects

Abstract: Several drugs have recently been reported to induce rapid antidepressant effects in clinical trials and rodent models. Although the cellular mechanisms involved remain unclear, reports suggest that increased glutamate transmission contributes to these effects. Here, we demonstrate that the antidepressant-like efficacy of three unique drugs, with reported rapid onset antidepressant properties, is coupled with a rapid transient rise in glutamate cycling in medial prefronal cortex (mPFC) of awake rats as measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 35 publications
4
112
0
1
Order By: Relevance
“…16,29,33,34 Studies in rodents show that ketamine produces a rapid and transient rise in glutamate re lease and cycling in the medial prefronal cortex (mPFC), which in turn leads to the acute activation of AMPA recep tors, properties proposed to mediate the rapid anti depressant effects of ketamine. 35,36 Subanesthetic doses of ketamine facili tate AMPARmediated synaptic transmission in the mPFC, as shown by intracellular recordings of AMPA induced cur rents in rat mPFC pyramidal neurons 37 as well as in the hip pocampus, as measured by extracellular recordings and microiontophoresis of rat CA3 pyramidal neurons. 38 One study found that ketamine applied to hippocampal slices po tentiated CA1 AMPARmediated evoked neurotransmission within 30 minutes, which could not be attributed to increased presynaptic release probability.…”
Section: Role Of Ampa Receptorsmentioning
confidence: 99%
“…16,29,33,34 Studies in rodents show that ketamine produces a rapid and transient rise in glutamate re lease and cycling in the medial prefronal cortex (mPFC), which in turn leads to the acute activation of AMPA recep tors, properties proposed to mediate the rapid anti depressant effects of ketamine. 35,36 Subanesthetic doses of ketamine facili tate AMPARmediated synaptic transmission in the mPFC, as shown by intracellular recordings of AMPA induced cur rents in rat mPFC pyramidal neurons 37 as well as in the hip pocampus, as measured by extracellular recordings and microiontophoresis of rat CA3 pyramidal neurons. 38 One study found that ketamine applied to hippocampal slices po tentiated CA1 AMPARmediated evoked neurotransmission within 30 minutes, which could not be attributed to increased presynaptic release probability.…”
Section: Role Of Ampa Receptorsmentioning
confidence: 99%
“…Inhibition of NMDARs specifically on GABAergic interneurons is predicted to induce a decrease in overall inhibition, leading to pyramidal cell disinhibition and an enhancement of excitatory glutamatergic neurotransmission in the medial prefrontal cortex (mPFC), and potentially other mood-relevant cortico-limbic brain regions 35 (see Figure 1). In rats, ketamine administration at sub-anesthetic doses results in a significant increase in extracellular glutamate levels 35 and an increase in glutamate cycling 44 in the prefrontal cortex. Further supporting this hypothesis, administration of partial inverse agonists at the benzodiazepine binding site of alpha5-containing GABA A receptors, which are selectively expressed in the forebrain, including prefrontal cortex and hippocampus, promote coherent network activity via disinhibition of excitatory neurotransmission 45 and exert rapid antidepressant actions in several animal tests 4648 .…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 99%
“…Although ketamine and scopolamine are expected to weaken excitatory neurotransmission via blocking NMDARs and mAChRs respectively, both drugs, at low doses, induce a rapid increase in extracellular glutamate levels [85, 147, 148] and an enhancement of glutamate cycling [149] in the mPFC of rodents. One hypothesis that can explain this paradoxical effect is that ketamine and scopolamine exert the effects via receptor subtypes localized on inhibitory GABAergic interneurons, resulting in a reduction in their action potential firing of these neurons.…”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…Therefore, ketamine appears to exert differential effects in vivo and in vitro in terms of LTP induction. One factor to consider in regard to this paradox is the lack of metabolism of ketamine to its HNK metabolites in vitro [214] and/or that enhanced glutamatergic neurotransmission (i.e., increased extracellular glutamate levels [147], increased glutamate cycling [149]) might not occur in slices. Another important factor is the relatively rapid (within 2 h post-injection) clearance of ketamine from the brain in vivo [45].…”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%